Analisis Kesulitan Guru dalam Menerapkan Penilaian Autentik di Sekolah Dasar Negeri - Fitri Ijarmana; Elpri Darta Putra (NATURALISTIC : Jurnal Kajian Penelitian Pendidikan dan Pembelajaran, 2021)
The purpose of this study is to describe the problem of teachers in applying authenticity at the 29 Pekanbaru State Elementary School. This type of research is descriptive qualitative research. The resource persons in this study were the principal and second grade teachers, fourth grade teachers and fifth grade teachers at the 29 Pekanbaru State Elementary School. Data collection techniques used are interviews, observation and documentation. The data analysis technique uses the Milles and Huberman model with stages, data reduction, data presentation, and drawing conclusions. The results showed that the Pekanbaru 29 Public Elementary School had assessed the authentic principle to assess student learning outcomes which included assessment, knowledge and skills. Attitude assessment uses direct observation techniques (observation) and self-assessment. Knowledge assessment in the form of written tests, assignments and questions in the Student Worksheet (LKS). Skills assessment using practice/performance techniques and products. The obstacles experienced by teachers in implementing authentic assessment are the use of assessment techniques on student attitudes, the use of written test techniques and assignments on knowledge competencies and the use of product techniques on skills.